Cannulation strategies & circulation management in type‐A aortic dissection. Issue 5 (17th March 2021) - Saran, Nishant; Pochettino, Alberto
Abstract: Type A aortic dissection most often requires emergent surgery to prevent malperfusion, stroke, and/or rupture of aorta. To achieve the structural goals of the operation, the conduct of the surgery is targeted from it inception at restoring true lumen flow. In this regard, institution of cardiopulmonary bypass and circulation management is key to allow adequate systemic flow, perfusion of brain and visceral organs and comprehensive systemic cooling to achieve circulatory arrest when needed. Different strategies have been used to establish adequate true lumen perfusion with varying success rates, with the most common still being femoral cannulation. More recently axillary and central cannulation strategies have shown satisfactory results by allowing more reliable true lumen flow. Cannulation approach should, therefore, depend on individual patient characteristics, presentation, and true lumen anatomy.